y = 3x – 5
y = 6x – 8
The quickest simplest way is to solve this system of 2 equation by SUBSTITITION:
1st Transpose x and y so that to be on the left side
-3x + y = -5
-6x +y = - 8
Now let's eliminate y: To do so multiply all term of the 1st equation by ( - 1) =>
-1(-3x + y = -5) ==> 3x - y = 5
Take the last equation and add it up to the 2nd"
3x - y = 5
-6x +y = - 8
---------- ----
-3x +0y = -3==> 3x = 3 and x =1
Last step, Replace x by its value (x=1) in any of the equation, let's take the second one for example
-6x +y = - 8 ==> -6(1) +y = -8 ==>-6 + y = -8 . Transpose (-6) to the right, it becomes +6 ==> y = -8 +6 ==> y =-2
x=1 & y=-2 are the solution of the system